Management of human resources for health : Report of a WHO Expert Committee, meeting held in Geneva, 3-9 November 1987 - WHO Expert Committee on Management of Human Resources for Health; World Health Organization (Geneva : World Health Organization, 1989)
Contemporary healthcare systems face several challenges. The main management challenges include shortage and low satisfaction of health professionals. Satisfaction and motivation of medical staff is crucial for their stabilization and quality work-medical performance. The positive impact of HRM practices on increasing employee satisfaction and engagement is scientifically proven. Currently, HRM practices in healthcare are used in a limited way, often only at the level of HR or labour law and union bargaining. This is indicative of the low level of HR development. It is desirable to make full use of HRM practices in healthcare. The aim of this paper is to identify and define the challenges of human resource management in healthcare and explain the importance of implementing developed HRM practices to improve the quality of health care delivery. The research method used is a literature search. The investigation of the relationship between quality human resource management and healthcare delivery is considered important because the knowledge and competency to manage people are not necessary to hold a management position in most healthcare professions in Slovakia. In the world$1 (Bs best hospitals, we find developed HRM with a positive impact on employee satisfaction and medical indicators.s
Introduction -- Scope and context of health personnel management -- Health personnel management : definition,components and principles -- The environment of health personnel management -- Towards better health personnel management : issues and approaches -- Strategies for improving health personnel management The role of WHO -- Recommendations
Keywords: Human resources; Health care; Management in health system